Yttria-ytterbia-gadolinia composite stabilized zirconia thermal barrier coating powder and method of making same
Patent Information
- Application Number
- CN202611171076.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-23
AI Technical Summary
然而,现有技术中多种稳定剂难以均匀进入氧化锆晶格形成高度均匀的固溶体,成为制约高性能复合稳定氧化锆粉体制备的核心难题
本发明并非单纯依靠纳米化结构降低涂层热导率,而是通过控制研磨粉末粒径和喷雾造粒结构。经检测,本发明的方法能够在粉体颗粒内部预先形成25%-30%的孔隙结构。该孔隙结构能够在等离子喷涂过程中部分转移并保留于涂层中,使涂层更容易获得适宜孔隙率,从而降低热导率并改善隔热性能。由于粉体内部含有不规则颗粒堆积形成的支撑骨架,喷涂过程中部分颗粒结构能够起到骨架支撑和应力缓释作用,有利于降低涂层因过度致密化产生的热应力集中风险,同时保持粉体流动性、喷涂适应性和涂层高温相稳定性。与仅依靠喷涂工艺调节孔隙率的方式相比,本发明能够从粉体结构层面直接调控涂层孔隙来源,工艺稳定性更好。
Smart Images

Figure CN122959657A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal barrier coating materials technology, and in particular to a yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder and its preparation method. Background Technology
[0002] Thermal barrier coatings are key thermal insulation coatings applied to the surfaces of hot-end components in aero-engines and ground-based gas turbines. They provide effective thermal protection to the metal substrate through a surface layer of low thermal conductivity ceramic materials, thereby significantly improving the service temperature and lifespan of the components. As aero-engines evolve towards higher thrust-to-weight ratios, lower fuel consumption, and longer lifespans, turbine inlet temperatures continue to rise, placing higher demands on the temperature resistance, phase stability, and thermal insulation performance of thermal barrier coatings.
[0003] While yttrium oxide-stabilized zirconia materials are widely used, they are prone to phase transformation and coating failure during long-term service at temperatures above 1200℃. Research indicates that using multiple rare-earth oxides to co-stabilize zirconia can simultaneously improve high-temperature phase stability and reduce thermal conductivity, with systems co-stabilized by ytterbium oxide and gadolinium oxide showing promising potential. However, in existing technologies, it is difficult for multiple stabilizers to uniformly integrate into the zirconia lattice to form a highly uniform solid solution, which remains a core challenge restricting the preparation of high-performance composite stabilized zirconia powders.
[0004] However, in existing thermal barrier coating powder designs, some schemes mainly rely on nanostructures to improve coating performance. But nanoparticles are prone to sintering and growth during high-temperature preparation and service, especially under long-term heat exposure conditions above 1200°C. The original fine structure is difficult to maintain stably, and the coating tends to become denser, which may lead to increased thermal conductivity and thermal stress concentration, increasing the risk of coating cracking or failure. On the other hand, thermal barrier coatings themselves need to maintain appropriate porosity to extend the heat conduction path and mitigate thermal stress. However, if porosity is adjusted only through plasma spraying parameters, the process window is narrow, and stability and repeatability are difficult to control.
[0005] Therefore, it is necessary to start from the powder's own structure and pre-construct a controllable pore structure and particle skeleton before spraying, so that the subsequent coating can more stably achieve the target porosity and low thermal conductivity. Based on this, further development of composite stable zirconia powders with both high phase stability and beneficial thermal insulation pore structure and their preparation methods is needed. Summary of the Invention
[0006] In view of this, the present invention provides a yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder and its preparation method. The present invention achieves uniform solid solution of the multi-component stabilizer through electrofusion synthesis, combined with spray granulation and high-temperature calcination to form a porous structure, thereby improving the phase stability and thermal insulation performance of the powder, and has broad application prospects in the field of hot-end components of aero-engines and gas turbines.
[0007] The first aspect of this invention is to provide a yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder. The powder is made from yttrium oxide, ytterbium oxide, gadolinium oxide and zirconia as raw materials, and is synthesized by electrofusion, crushing and grinding, spray granulation and high temperature calcination. The powder is spherical powder, and the coating prepared by plasma spraying has a porous structure and the thermal conductivity of the coating is <1.0 W / (m·K).
[0008] A second aspect of the present invention is to provide a method for preparing the above-mentioned yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder, comprising the following steps: S1. Ingredient mixing: Yttrium oxide, ytterbium oxide, gadolinium oxide, and zirconium oxide are mixed evenly in proportion to obtain a mixed powder; S2, Electrofusion Synthesis: The mixed powder obtained in step S1 is placed in an electric melting furnace for high-temperature melting treatment, so that yttrium oxide, ytterbium oxide, gadolinium oxide and zirconium oxide are fully melted. During the cooling process, yttrium oxide, ytterbium oxide and gadolinium oxide completely enter the zirconium oxide lattice to form a composite stable zirconium oxide solid solution. The electrofusion product is obtained after cooling. S3. Crushing and grinding: The fused product obtained in step S2 is crushed and ground to obtain ground powder; S4. Spray granulation: The grinding powder obtained in step S3 is mixed with dispersant, binder and water to prepare a slurry, and then granulated using a spray granulator to obtain spherical agglomerated powder; S5. High-temperature calcination: The spherical agglomerated powder obtained in step S4 is subjected to high-temperature calcination at 1000℃-1600℃ to form a sintered body between the primary particles, thereby improving the mechanical strength of the agglomerated particles. At the same time, the organic components are removed while the pore structure inside the agglomerated particles is retained, resulting in calcined spherical powder. The spherical agglomerated powder obtained in step S5 has interparticle pores inside; these pores mainly come from the accumulation voids formed by the particles during the spray granulation process and the voids formed after the decomposition of organic components during calcination. These pores can be partially retained in the coating during the subsequent plasma spraying process, forming a microstructure that is beneficial to reducing the thermal conductivity of the coating. S6. Sieving: The powder calcined in step S5 is sieved to obtain yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder with the target particle size.
[0009] In step S1, the zirconium oxide is monoclinic zirconium oxide; the purity of yttrium oxide, ytterbium oxide, and gadolinium oxide is not less than 99.9%; the mixed powder composition by mass percentage is as follows: 8%-12% yttrium oxide, 3%-8% ytterbium oxide, 3%-8% gadolinium oxide, with the balance being zirconium oxide; Preferably, in step S2, the temperature of the electrofusion treatment is 2500℃-3500℃ to ensure that the raw materials form a uniform melt; the monoclinic phase content of zirconium oxide in the electrofusion treatment product is <10%; and the cooling is at least one of natural cooling, compressed air cooling, and water cooling.
[0010] Preferably, in step S3, the D of the ground powder 50 <5 μm, more preferably <3 μm; the crushing and grinding is at least one of jaw crusher, roller crusher, and air jet mill.
[0011] Preferably, in step S4, the dispersant is ammonium polyacrylate, and its dosage is 0.01-1.0 wt.% of the mass of the ground powder; the binder is at least one of polyvinyl alcohol, polyethylene glycol, and gum arabic, and the dosage of the binder is 0.1-5 wt.% of the mass of the ground powder; the solid content of the slurry is 40 wt.%-80 wt.%; the inlet temperature of the spray granulation is 200℃-300℃, and the outlet temperature is 100℃-150℃.
[0012] This invention controls the particle size distribution of the ground powder through a crushing and grinding process, forming micron-sized irregular particles suitable for spray granulation. These irregular particles can overlap and form a stable internal framework structure during agglomeration, which is more beneficial for preserving interparticle porosity within spherical powders compared to dense agglomerates formed entirely by nanoparticles.
[0013] Preferably, the internal porosity of the spherical agglomerated powder can be controlled at 25%-30%, which can be controlled by the grinding particle size, slurry solid content, binder addition amount, spray granulation parameters, and high-temperature calcination temperature and holding time.
[0014] Preferably, in step S5, the high-temperature calcination temperature is 1000℃-1600℃, more preferably 1200℃-1500℃, and the holding time is 1-15 h.
[0015] Preferably, in step S6, the sieving is performed using a vibrating screen, an air classifier, or an air classifier.
[0016] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention does not simply rely on nanostructuring to reduce coating thermal conductivity, but rather controls the particle size of the ground powder and the spray granulation structure. Testing has shown that the method of this invention can pre-form a 25%-30% porosity structure within the powder particles. This porosity structure can be partially transferred and retained in the coating during plasma spraying, making it easier for the coating to achieve a suitable porosity, thereby reducing thermal conductivity and improving thermal insulation performance. Because the powder contains a supporting framework formed by irregular particle accumulation, some of the particle structure can act as a framework support and stress relief during spraying, which helps reduce the risk of thermal stress concentration caused by excessive densification of the coating, while maintaining powder flowability, spray adaptability, and high-temperature phase stability of the coating. Compared to methods that rely solely on the spraying process to adjust porosity, this invention can directly control the source of coating porosity at the powder structure level, resulting in better process stability.
[0017] This invention optimizes the ratio of multi-element rare earth oxides and employs an electrofusion synthesis process to achieve highly uniform solid solution of stabilizers in the zirconium oxide lattice, thereby effectively improving the phase stability of the powder. By combining crushing and grinding, spray granulation, and high-temperature calcination processes, powders with good sphericity and excellent flowability are prepared. At the same time, a rich pore structure is formed inside the powder, which is partially retained in the subsequent plasma spraying process, significantly reducing the thermal conductivity of the coating. The overall process route is simple, the raw materials are readily available, and it is suitable for industrial-scale production. It provides a new material with excellent performance and easy application in the field of high-temperature thermal barrier coatings, and has broad application prospects in the field of hot-end components of aero-engines and gas turbines. Attached Figure Description
[0018] The present invention will be further described below with reference to the accompanying drawings.
[0019] Figure 1 The X-ray diffraction (XRD) pattern of the electrofused product obtained after electrofusion synthesis in step S2 of Example 1 of the present invention; Figure 2 This is a scanning electron microscope (SEM) image of the cross-section of the thermal barrier coating powder particles prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope (SEM) image of a single particle cross-section of the yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder prepared in Example 1 of the present invention. Figure 4 This is a magnified scanning electron microscope image of the internal pore structure of the yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder prepared in Example 1 of the present invention. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] Unless otherwise specified, all experiments were repeated three times, and the results are expressed as averages.
[0022] Example 1: A method for preparing a yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder, comprising the following steps: S1. Ingredient Mixing: Weigh 9.5 kg of yttrium oxide (Y2O3, purity 99.9%), 5.6 kg of ytterbium oxide (Yb2O3, purity 99.9%), 5.2 kg of gadolinium oxide (Gd2O3, purity 99.9%), and 79.7 kg of monoclinic zirconium oxide (ZrO2, purity 99.5%) according to the mass percentage, and mix them in a V-type mixer for 3 h to obtain a mixed powder. S2. Electrofusion Synthesis: The uniformly mixed raw materials are added to an electric melting furnace and melted at 2800℃ until completely melted, allowing yttrium oxide, ytterbium oxide, and gadolinium oxide to fully enter the zirconium oxide lattice. After natural cooling, the electrofused material is removed and analyzed by X-ray diffraction. The results are as follows: Figure 1 As shown.
[0023] Depend on Figure 1 It can be seen that the monoclinic phase diffraction peak intensity of zirconium oxide in the electrofused product is extremely weak, and the monoclinic phase content is 3%. This indicates that after electrofusion treatment, yttrium oxide, ytterbium oxide, and gadolinium oxide have fully entered the zirconium oxide lattice, forming a highly uniform composite stable zirconium oxide solid solution, and the monoclinic phase content is significantly reduced. S3. Crushing and Grinding: The fused alumina material is first coarsely crushed using a jaw crusher, then further crushed using a double roll crusher, and finally ground in an air jet mill to obtain D. 50 =1.2 μm grinding powder; S4. Spray granulation: The ground powder is mixed with 3 wt.% polyvinyl alcohol, 0.5 wt.% ammonium polyacrylate, and water to prepare a slurry with a solid content of 70 wt.%. Granulation is performed using a centrifugal spray granulator with an inlet temperature of 250℃ and an outlet temperature of 110℃ to obtain spherical agglomerated powder. S5. High-temperature calcination: Place the spherical agglomerated powder in a high-temperature pusher kiln and calcine it at 1350℃ for 5 h; S6. Sieving: The calcined powder is sieved using a vibrating screen to obtain yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder with a particle size of 15-106 μm.
[0024] Depend on Figure 2 It can be seen that the powder particles prepared in this embodiment are spherical with good sphericity and have obvious porous structure inside. This porous structure is formed by the voids formed inside the particles during spray granulation and the pores left after the decomposition of organic components during high-temperature calcination. This is beneficial for retaining pores in the coating after plasma spraying, thereby reducing the thermal conductivity of the coating.
[0025] Further integration Figure 3 and Figure 4 As can be seen, the spherical powder prepared in this embodiment is not a completely dense structure. Its interior is formed by the accumulation of irregular ceramic particles, with relatively obvious pores and a supporting framework between the particles. Image observation shows that the internal pore structure is relatively uniformly distributed, with a porosity controllable between 25% and 30%. This structure, on the one hand, prevents the powder from becoming completely dense during subsequent plasma spraying, and on the other hand, allows some pores to remain within the coating during the spraying process, thus forming a porous coating structure that helps reduce thermal conductivity. Because the internal framework is composed of micron-sized irregular particles, compared to a simple nanoparticle agglomeration structure, it is less prone to complete sintering and collapse during high-temperature calcination and spraying, which helps maintain the stability of the coating's pore structure and provides a certain stress release effect during thermal cycling.
[0026] The powder prepared in this embodiment was tested and found to have a flowability of 44 s / 50 g and a bulk density of 2.1 g / cm³. 3 The thermal barrier coating prepared by plasma spraying using this powder showed excellent high-temperature phase stability after heat treatment at 1300℃ for 200 h, with no monoclinic phase detected. Cross-sectional observation of the coating revealed a uniformly distributed pore structure, and the thermal conductivity of the coating was measured to be 0.82 W / (m·K).
[0027] Example 2 The difference from Example 1 is that: in step S1, 9.2% yttrium oxide, 5.7% ytterbium oxide, and 5% gadolinium oxide are weighed by mass percentage, with the remainder being monoclinic zirconium oxide; in step S2, the electric melting temperature is 2500℃; and in step S5, the high-temperature calcination temperature is 1000℃.
[0028] Testing revealed that the monoclinic phase content of zirconium oxide in the fused product prepared in this embodiment was 4%; the powder flowability was 40 s / 50 g; and the loose packing density was 2.15 g / cm³. 3 The thermal barrier coating prepared by plasma spraying using this powder, after heat treatment at 1300℃ for 200 h, has a monoclinic phase content of 5% and a thermal conductivity of 0.8 W / (m·K).
[0029] Example 3 The difference from Example 1 is that: in step S1, 9.6% yttrium oxide, 5.5% ytterbium oxide, and 5.5% gadolinium oxide are weighed by mass percentage, with the remainder being monoclinic zirconium oxide; in step S2, the electric melting temperature is 3500℃; and in step S5, the high-temperature calcination temperature is 1600℃.
[0030] Testing revealed that the monoclinic phase content of zirconium oxide in the fused product prepared in this embodiment was 2%; the powder flowability was 38 s / 50 g, and the loose packing density was 2.09 g / cm³. 3 The thermal barrier coating prepared by plasma spraying using this powder, after heat treatment at 1300℃ for 200 h, had a monoclinic phase content of 4% and a thermal conductivity of 0.76 W / (m·K).
[0031] Example 4 The difference from Example 1 is that in step S3, the fused agglomerate material is crushed and ground to a median particle size D. 50 It is 2.5 μm.
[0032] The powder prepared in this embodiment was tested and found to have a flowability of 47 s / 50g and a bulk density of 1.98 g / cm³. 3 The thermal conductivity of the coating was measured to be 0.72 W / (m·K).
[0033] Comparative Example 1 The difference from Example 1 is that ytterbium oxide and gadolinium oxide are not added in the ingredients of step S1, only 8% by mass of yttrium oxide is added, and the balance is monoclinic zirconium oxide (i.e., conventional 8YSZ formulation).
[0034] According to the test results, the content of monoclinic phase in the powder prepared in this comparative example was 6% after heat treatment at 1300℃ for 200 h, and the thermal conductivity of the coating was 1.2 W / (m·K).
[0035] Comparative Example 2 The difference from Example 1 is that step S2, the electrofusion synthesis step, is omitted. Instead, the mixed powder from step S1 is directly subjected to the crushing and grinding process in step S3 to D. 50 =1.2 μm, and then spray granulation and high-temperature calcination were carried out under the same conditions.
[0036] Testing revealed that the monoclinic phase content of zirconium oxide in the powder prepared in this comparative example was 100%. After heat treatment at 1300℃ for 200 h, the monoclinic phase content was 26%, and the coating thermal conductivity test result was 1.3 W / (m·K).
[0037] Comparative Example 3 The difference from Example 1 is that in step S3, the fused agglomerate material is crushed and ground to a median particle size D. 50 It is 8.5 μm.
[0038] Testing revealed that the powder prepared in this comparative example had extremely poor sphericity, almost failing to form a solid mass. Because the particles were dense and settled quickly, the powder lacked flowability, with a loose bulk density of 1.65 g / cm³. 3 Material cannot be fed during the spraying process.
[0039] Comparative Example 4 ① The difference from Example 1 is that the high-temperature calcination temperature in step S5 is 800℃.
[0040] Testing revealed that the powder particles lacked strength because the binder had decomposed and been discharged, and the sintering temperature had not been reached. Most of the particles were pulverized during the sieving process, with a loose packing density of 1.55 g / cm³. 3 Powder cannot be sprayed.
[0041] ② The difference from Example 1 is that the high-temperature calcination temperature in step S5 is 1750℃.
[0042] Tests showed that after the powder was sintered at 1750℃, it had become porcelain and all of it was sintered together into a large block that could not be separated, making it impossible to complete the spraying test.
[0043] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder, characterized in that, The powder is made from yttrium oxide, ytterbium oxide, gadolinium oxide and zirconium oxide as raw materials, and is synthesized by electrofusion, crushing and grinding, spray granulation and high temperature calcination. The powder is spherical powder, and the coating prepared by plasma spraying has a porous structure and the thermal conductivity of the coating is <1.0W / (m·K).
2. The method for preparing the yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder according to claim 1, characterized in that, Includes the following steps: S1. Ingredient mixing: Yttrium oxide, ytterbium oxide, gadolinium oxide, and zirconium oxide are mixed evenly in proportion to obtain a mixed powder; S2, Electrofusion Synthesis: The mixed powder obtained in step S1 is placed in an electric melting furnace for high-temperature melting treatment, and then cooled to obtain the electrofusion product; S3. Crushing and grinding: The fused product obtained in step S2 is crushed and ground to obtain ground powder; S4. Spray granulation: The grinding powder obtained in step S3 is mixed with dispersant, binder and water to prepare a slurry, and then granulated using a spray granulator to obtain spherical agglomerated powder; S5. High-temperature calcination: The spherical agglomerated powder obtained in step S4 is subjected to high-temperature calcination to obtain calcined spherical powder. S6. Sieving: The powder calcined in step S5 is sieved to obtain yttrium oxide-ytterbium oxide-gadolinium oxide composite stabilized zirconia thermal barrier coating powder.
3. The preparation method according to claim 2, characterized in that, In step S1, the zirconium oxide is monoclinic zirconium oxide; by mass percentage, the mixed powder composition is as follows: yttrium oxide 8%-12%, ytterbium oxide 3%-8%, gadolinium oxide 3%-8%, with the balance being zirconium oxide.
4. The preparation method according to claim 2, characterized in that, In step S2, the temperature of the electrofusion treatment is 2500℃-3500℃.
5. The preparation method according to claim 2, characterized in that, In step S2, the monoclinic phase content of zirconium oxide in the electrofusion product is <10%.
6. The preparation method according to claim 2, characterized in that, In step S3, the D of the grinding powder 50 <5μm.
7. The preparation method according to claim 6, characterized in that, In step S3, the D of the grinding powder 50 <3μm.
8. The preparation method according to claim 2, characterized in that, In step S4, the solid content of the slurry is 40wt.%-80wt.%.
9. The preparation method according to claim 2, characterized in that, In step S5, the high-temperature calcination temperature is 1000℃-1600℃, and the holding time is 1-15 h.
10. The preparation method according to claim 9, characterized in that, In step S5, the high-temperature calcination temperature is 1200℃-1500℃.